Rheological and chemical characteristic of warm asphalt rubber binders and their liquid phases. (30th December 2018) - Wang, Duanyi; Li, Danning; Yan, Jinhai; Leng, Zhen; Wu, Yueming; Yu, Jiangmiao; Yu, Huayang
Highlights: A separating system was designed to remove the insoluble CRM particles. The rheological properties of AR/WAR and their liquid phases were compared. The contributions of particle effect and polymer modification to rutting and fatigue performances were revealed. The effects of two WMA additives and two mixing procedures were evaluated. Abstract: Warm asphalt rubber (WAR) is a sustainable paving material combining the merits of warm mix asphalt (WMA) and asphalt rubber (AR). The performance improvement on rutting and fatigue resistance of WAR has been well acknowledged. However, research on analyzing the performance enhancing mechanism is relatively limited. The objective of this research is to study the contribution of two aspects on its enhanced rheological properties, i.e., 1) the dissolution of crumb rubber modifier (CRM) and WMA additives, and 2) the particle effect of insoluble CRM. To this end, the liquid phases of AR and four WAR binders (with two WMA additives and two mixing sequences) were obtained by removing the CRM particles. Superpave rutting and fatigue tests were conducted on the above-mentioned five binders and their corresponding liquid phases. Rheological analysis revealed that the enhanced rutting resistance of AR is contributed by both the polymer modification effect of the soluble CRM components and the particle effect of the insoluble parts. However, the improved fatigue performance is mostly attributed to CRM's particle effect. The type and mixing sequence of WMA additives also have noticeable influence on the rheological properties of the binder liquid phases. Finally, gel permeation chromatography (GPC) analysis indicated that the molecular distributions of liquid phases of the WAR binders are also affected by both the type and mixing sequence of WMA additives.